On the domains of T4 phage sliding clamp gp45: An intermolecular crosstalk governs structural stability and biological activity - Singh, Manika Indrajit; Ganesh, Bylapudi; Jain, Vikas (Biochimica et biophysica acta. General subjects, 2017)
DNA polymerase processivity factors are ubiquitously present in all living organisms. Notwithstanding their high significance, the molecular details of clamps pertaining to the factors contributing to their stability are presently lacking. The bacteriophage T4 sliding clamp gp45 forms a homotrimer that besides being involved in DNA replication, moonlights as a transcription factor. Here we have carried out a detailed characterization of gp45 to understand the role of monomer-monomer interface interactions in stability and functioning of the protein. We generated several gp45 mutants harboring either Ala or Pro substitutions at the interface residues and performed a detailed investigation using biochemical and biophysical methods including circular dichroism, fluorescence anisotropy and quenching, differential scanning calorimetry, blue-native PAGE, cross-linking, size exclusion chromatography, and dynamic light scattering. We also carried out both transcription and DNA replication to understand the properties of the wild-type and the mutant proteins. One specific mutation S88P leads not only to monomerization, but also results in an unstable molecule. Most interestingly, mutating either Q125 or K164 in the gp45 C-terminal domain negatively affects the stability of the N-terminal domain. We also report that these residues upon mutation to alanine make gp45 inactive for late promoter transcription, whereas strand-displacement DNA replication ability remains unaltered. The results suggest that the two domains of gp45 demonstrate an “inter-monomer” crosstalk that stabilizes the trimer. We also conclude that the residue-specific interactions at the interface allow the protein to function distinctly as replication and transcription factors. [Display omitted] •Bacteriophage T4 homotrimeric sliding clamp gp45 is stable only as a trimer.•Perturbing interface interaction causes lowering of thermal & chemical stabilities.•gp45 adopts ‘molten globule’-like intermediate state during chemical unfolding.•N-ter and C-ter domains affect each other's topology by an inter-domain crosstalk.•Interactions with CTD scaffold are necessary for gp45 trimerization and NTD folding.